A study on containment of heavy metals using soils and cellulose materials inside geotextile tubes. Issue 3 (13th March 2017) - Rupakheti, P.; Bhatia, S. K.
Abstract : The aim of this study is to explore effective containment of heavy metal solutions using geotextile dewatering technology. For that purpose, first the heavy metal solution (containing Pb 2+, Cu 2+, Cd 2+, Zn 2+ ) was mixed with soil sediments (Tully coarse and Tully fines) and cellulosic materials (jute fibers, peanut hulls, and kraft pulp). The mixing of the metal solution with soil and cellulose materials is believed to facilitate adsorption of metal ions from the solution into the surface of the solids. The dewatering behavior of the slurry (soil-heavy metal solution-cellulose materials) was studied using a pressure filtration test (PFT) in the lab. The concentration of filtrate collected from PFT, measured using inductively coupled plasma optical emission spectrometry (ICP-OES), showed that more than 95% of Pb, 90% of Cu, 80% of Cd, and 75% of Zn was contained and retained by the soil sediments and cellulose materials. The addition of cellulose materials provided additional benefits in dewatering. Among the three cellulosic materials, the addition of jute was able to reduce the water content of the filter cake by 44%. Since kraft pulp had a tendency to adsorb water and swell, water content as high as 40% was seen. All the cellulosic materials were also successful in improving the overall turbidity of the filtrate. A drop in turbidity of more than 60–80% was observed with the addition of peanut hulls. It was also observed that the optimum dose of polymer required was significantly low. A drop in optimum dose of more than 50% was observed using this technique.